The type and dosage of exercise therapy to facilitate the recovery from stroke for balance, walking and quality of life: a systematic review and meta-analysis of randomized controlled trials. (14th October 2021) - Amanzonwe, R E; Kossi, R O; Tedesco Triccas, L; Codjo, L H; Feys, P; Hansen, D; ,
Abstract: Background: Exercise therapy (aerobic or resistance therapy) could have a beneficial effect on balance, walking and quality of life (QoL). Objective: This systematic review and meta-analysis aimed to quantify the effects of different modes, dosages and setting of exercise therapy on balance, walking capacity and QoL in stroke survivors. Methods: We searched PubMed, CINHAL and Hinari to identify randomized controlled trials (RCT) that investigated the effects of aerobic (AT) and/or resistance therapy (RT) on balance, walking and QoL in stroke survivors. The treatment effect was computed by the standard mean differences (SMDs). Results: We included 27 RCT comprising 1, 549 chronic stroke survivors. Any modality was effective to improve balance. There was high-level evidence that AT interventions were most effective in improving walking capacity (SMD=0.36 [0.06, 0.66], p=0.02). Both AT, and AT combined with RT were effective to improve QoL (SMD=0.39 [0.09, 0.69], p=0.01). RT programs were not effective to improve walking and QoL. For walking capacity, a lower volume weekly (<60 minutes/session or <3 session/week) and higher intensity (>60% heart rate reserve; rate of perceived exertion (6–20) >14) of AT and RT exercises demonstrated significant higher effect. Hospital located rehabilitation settings trended to improve walking (SMD=0.23 [0.00, 0.45], p=0.05), when compared to home/community and laboratory settings. Conclusions: In chronic stroke, in particular AT executed in hospital located settings, with a lower volume and high intensity seems more effective strategy to facilitate walking capacity and improve QoL and should thus be incorporated into rehabilitation programs for stroke. Funding Acknowledgement: Type of funding sources: None.